Validity of problem-based learning biodiversity e-book integrating Ruwat Petirtaan Jolotundo's local wisdom for science literacy - Yusnita Ivaningtias; Sifak Indana; Novita Kartika Indah (University of Muhammadiyah Malang, 2024)
The problems faced in school textbooks and student worksheets are common problems globally and there are no daily problems that are in accordance with the surrounding environment and current problems so that they do not train students' scientific literacy skills. This research focuses on validity and readability of developing an integrated e-book that incorporates Jolotundo temple local wisdom into Biodiversity material to enhance high school students' Science Literacy skills. The study addresses the challenge of limited teaching materials due to the shortage of teachers capable of preparing suitable content for 21st-century learning, which emphasizes Science Literacy. The Research and Development (R&D) method was employed using the ADDIE framework, encompassing analysis, design, development, implementation, and evaluation stages. Data was collected through validation by two biology lecturers, material experts, and media experts, as well as a readability test. The e-book received high validation scores: 3.65 for presentation, 3.66 for content appropriateness, and 3.72 for language appropriateness. The readability test indicated a level 10, aligning with the cognitive level of grade X high school students, and was categorized as very positive and appropriate. In conclusion, the integrated e-book is highly feasible and valid for enhancing science literacy skills in grade X high school students, making it an effective tool for 21st-century learning.